Assessment of Mental Stress Among Undergraduate Medical Students Using GHQ-12: Mental stress among medical students (Journal of the Medical College for Women & Hospital, 2026)
Background: Medical education is one of the most demanding academic fields, often linked with high levels of mental stress among students. Early detection and management of psychological distress are essential to ensure the well-being of future healthcare professionals. Aim: To assess the prevalence of mental stress among undergraduate medical students using the 12-item General Health Questionnaire (GHQ-12) and to identify associated socio-demographic and academic factors. Materials and Method: A cross-sectional study was conducted among 150 undergraduate medical students of Enam Medical College from July 2025 to October 2025. Data were collected through a structured questionnaire including socio-demographic information, academic stress factors, and the GHQ-12 scale. Scoring was done using the 0-0-1-1 method, with scores ≥3 indicating psychological distress. Data were analyzed using SPSS, applying descriptive and chi-square tests. Results: Among the respondents, 73.3% were classified as psychologically distressed (GHQ-12 ≥3). Most students were aged 20–22 years (56%), and 58% were female. Major stress-related factors included heavy academic workload (68.6%), inadequate sleep (63.3% slept 0.05). Conclusion: A high prevalence of psychological distress was observed among medical students, driven mainly by academic burden, sleep deprivation, and limited recreational opportunities. Institutional measures such as accessible counseling, stress management programs, and supportive mentorship are urgently needed to promote student well-being.J Med Coll Women Hosp.2026; 22(1): 80-88